2017
DOI: 10.1364/josaa.34.000498
|View full text |Cite
|
Sign up to set email alerts
|

Accurate wavelength calibration method for compact CCD spectrometer

Abstract: Wavelength calibration is an important step in charge-coupled device (CCD) spectrometers. In this paper, an accurate calibration method is proposed. A model of a line profile spectrum is built at the beginning, followed by noise reduction, bandwidth correction, and automatic peak-seeking treatment. Experimental tests are conducted on the USB4000 spectrometer with a mercury-argon calibration light source. Compared with the traditional method, the results show that this wavelength calibration procedure obtains h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Wavelength calibration is obtained by exposing the optical system to a calibration light source or sources. Three aspects are critical for obtaining a proper wavelength calibration including (i) the selection of the calibration light, (ii) the determination of the center of characteristic peaks, and (iii) polynomial fitting to the data [ 39 ]. The calibration light source(s) should cover the wavelength range to be calibrated.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Wavelength calibration is obtained by exposing the optical system to a calibration light source or sources. Three aspects are critical for obtaining a proper wavelength calibration including (i) the selection of the calibration light, (ii) the determination of the center of characteristic peaks, and (iii) polynomial fitting to the data [ 39 ]. The calibration light source(s) should cover the wavelength range to be calibrated.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…In the works of other authors, it is shown that CCD-based spectrometers have a number of spectrum distortions, such as nonlinear pixel sensitivity to incident light [ 23 ] and chromatic distortions [ 24 , 25 , 26 ]. In these works, the sources of these errors are considered, as well as the methods of their compensation.…”
Section: Problem Explanationmentioning
confidence: 99%
“…It is required to conduct a wavelength calibration when using a CCD spectrometer to determine the corresponding pixel location of each wavelength prior to use [28]. We used a high-end desktop spectrometer (Perkin Elmer Lambda 950) as a secondary standard to determine the wavelength accuracy of our CCD spectrometer.…”
Section: Theorymentioning
confidence: 99%